PEMANFAATAN DAUN KELOR SEBAGAI SOLUSI KREATIF PENCEGAHAN STUNTING DI DESA UMBULREJO UMBULSARI JEMBER - Wildan Reza Priestyaji; Faisol Hakim; Amak Fadholi; Imra’atus Shalihah; Bustanul Arifin; Caleysda Aprilianti; R. Ilham Ahsan Nurrasyid; Muhammad Bintang Hayundavz; Asto Budianto; Camelia Gladis Larasati; Andita Dwi Faradila; Khusnul Khotimah; Wilkhanzia Asti Ananta; Anita Ningsih; Achmad Faisol Atho'illah Rasidi; Wulan Gustiranda; Puput Yuliani (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Stunting is a severe health issue that affects the development of children under five. Umbulrejo Village, Jember, has a significant stunting prevalence, with 10% of 250 toddlers affected. This community service program aims to prevent stunting through the innovation of a supplemental food in the form of cookies made from Moringa leaves, which are rich in nutrients such as calcium, iron, and vitamins A and C. The cookie production process involved several stages, including drying and grinding the Moringa leaves, as well as educating the community, particularly PKK members, about the benefits of Moringa. Evaluation results showed that 36 PKK members and toddlers in Umbulrejo Village enjoyed the product, indicating Moringa leaves' potential as an effective supplemental food for stunting prevention. The program's success is demonstrated by increased community knowledge and the toddlers' willingness to consume the Moringa leaf cookies.